Improving the Management of School Operational Assistance (SOA) Grants Through Expenditure Governance - Abdullah, M. Ikbal; Masdar, Rahma; Karim, Fikry; Din, Muhammad; Zahra, Femilia; Furqan, Andi Chairil; Munawarah, Munawarah; Iqbal, Muhammad; Masruddin, Masruddin; Hadi, Suryadi; Betty, Betty; Meldawati, Lucyani; Naida, Nasrun; Megawati, Nani (Economic and Business Horizon, 2022)
School Operational Assistance (SOA) is a government program that provides funding for personnel operational costs for basic education units as implementing compulsory learning programs. The SOA program policy, programmed in elementary and junior high schools, is one form of policy implementation with the aim of equity and improving the quality of basic education. Therefore, SOA funds must be managed properly and carried out orderly and responsibly. The management of SOA funds is the principal’s responsibility, assisted by the SOA Treasurer. However, in practice, there was a misappropriation of SOA funds. The misappropriation of SOA funds was found to several factors that lead to the achievement of the objectives of managing funds have not been achieved, including planning aspects, implementation aspects, and accountability aspects. In the implementation aspect, it was found that, basically, all use of the budget was in accordance with the technical guidelines. Still, the lack of socialization among parents caused many parties to misunderstand the problem of SOA funds, even though socialization is a very important stage in determining the success and smooth implementation of the program. In accountability, not a few schools have difficulty compiling financial reports because not all schools have competent personnel in their fields. Furthermore, in the 2021 Supreme Audit Agency’s (BPK/Badan Pemeriksa Keuangan) audit report, there are findings obtained by Supreme Audit Agency, one of which is that there are weaknesses in the administration and accountability of School Operational Assistance funds (SOA) in Tojo Una Una, Central Sulawesi, Indonesia. Therefore, it is necessary to do service in the form of socialization related to the administration of the SOA Fund Treasurer, which will be framed in an effective communicative and relaxed manner so that it can provide a stimulus to participants so that they can comprehensively understand administrative technicalities in accordance with the latest developments in the Regulation of the Minister of Internal Affairs No. 24 of 2020 concerning administration for the management of SOA grants.